HEAVY METAL CONTENTS AND OTHER PHYSICAL QUALITY INDICES OF SEWERAGE, CANAL AND DRINKING WATERS - Mehmood, Sara; Sattar, Abdus; ullah, Ihsan; Atta, Shaheen; Nawaz, Tariq; Arif, Samina (Biological Sciences - PJSIR, 2001)
Analysis of Cd, Pb and Cu in canal, sewerage and drinking waters by potentiometric stripping analysis (PSA) is described. Other quality indices of waters such as temperature, pH, EC and total solid were also determined. The levels of heavy metal contents of sewerage, canal and drinking waters revealed marked differences and wide coefficient of variability (CV). Generally Cd and Pb contents were higher in sewerage than canal and drinking waters. However, Cu content of drinking waters was higher than other waters tested. The total solids were found to be generally higher in sewerage and canal waters than drinking waters. The variations in temperature, pH and EC were marginal to marked depending upon the source and the location.